Textiles, Tattoos, and Tradition: Cultural Expressions in Naga Society - Bideno R Ezung (Journal of International Islamic Law, Human Right and Public Policy, 2026)
The cultural heritage of the Naga communities of Northeast India represents a rich tapestry of indigenous traditions, artistic practices, and social identities. Among the most significant expressions of Naga culture are textiles, tattoos, and customary traditions, each of which functions as a marker of identity, status, memory, and community belonging. This article examines how these cultural forms have historically shaped social life among various Naga tribes and how they continue to evolve in the context of colonial influence, Christianity, modernization, and globalization. Traditional textiles communicate social hierarchy, clan affiliation, and aesthetic values through distinctive motifs and weaving techniques. Similarly, tattooing practices, particularly among tribes such as the Konyak Nagas, served as symbols of bravery, achievement, and ritual identity. Alongside these artistic forms, indigenous traditions such as festivals, oral narratives, and communal institutions have played an essential role in preserving collective memory and cultural continuity. The article argues that textiles, tattoos, and traditions are not merely decorative or symbolic practices but living archives of Naga history and identity. Despite social transformation and external influences, these cultural expressions continue to remain central to contemporary discussions of indigenous heritage and cultural preservation in Northeast India.